High-stability maleic anhydride hydrogenation catalyst and preparation method thereof

CN122999264APending Publication Date: 2026-10-30JIANGNAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924548.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种高稳定性顺酐加氢催化剂及其制备方法,以解决现有技术中存在的问题

Benefits of technology

1、本发明引入高熵合金作为顺酐加氢催化剂的金属活性中心。以镍、铜、钯、铁、钴五种金属盐为前驱体,经分解还原形成金属纳米颗粒,该反应过程温和,无有害或难处理物质产生。金属镍、钯、铜是加氢催化的常用活性组分,而金属铁、钴可与前三种金属元素形成稳定的固溶体相,经金属前驱体形成的高熵合金能提高主产物的选择性,降低副反应,从而提高催化剂的反应效率。同时,金属钯虽然具有良好的加氢催化活性,但成本高昂,以高熵合金的形式存在,能够降低贵金属的使用量,降低生产成本,而且制备得到的顺酐加氢催化剂的催化效果优于贵金属催化剂。此外,高熵合金严重的晶格畸变使原子扩散的势能增大,表面原子扩散受阻,赋予催化剂更高的稳定性。高熵合金中的多种金属元素能够协同发挥作用,调节催化剂的电子结构,为顺酐加氢反应提供了丰富的活性位点,使顺酐加氢催化剂具有更高的活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a high-stability maleic anhydride hydrogenation catalyst and a preparation method thereof, and relates to the technical field of catalyst preparation, and comprises the following steps: adding a metal salt into a solvent, and magnetically stirring to obtain a precursor metal salt solution; performing ultrasonic dispersion treatment on MFI zeolite, adding the precursor metal salt solution, ultrasonic mixing, freeze-drying, heating to 500-600 DEG C at a rate of 5-10 DEG C / min under an argon-hydrogen mixed atmosphere, and keeping warm to obtain the maleic anhydride hydrogenation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation technology, specifically a highly stable maleic anhydride hydrogenation catalyst and its preparation method. Background Technology

[0002] Maleic anhydride, or maleic anhydride, is an important chemical raw material and intermediate. It is composed of C=C, C=O, and epoxy bridge bonds. Under different reaction conditions, it can be used to synthesize downstream products such as succinic anhydride, succinic acid, and 1,4-butanediol through hydrogenation. Succinic anhydride is widely used in surfactants, food additives, pharmaceuticals, and pesticides. Currently, the main methods for synthesizing succinic anhydride are the succinic acid dehydration method and the maleic anhydride hydrogenation method. Due to its simple operation and continuous production capability, the maleic anhydride hydrogenation process has become the commonly used industrial method for preparing succinic anhydride. Commercially available catalysts for maleic anhydride hydrogenation reactions are mainly nickel-based, copper-based, and palladium-based. However, these catalysts all suffer from problems such as excessive byproducts, easy loss of active components, poor chemical stability, and easy carbon deposition and deactivation.

[0003] Therefore, developing a highly stable maleic anhydride hydrogenation catalyst is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a highly stable maleic anhydride hydrogenation catalyst and its preparation method, so as to solve the problems existing in the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a highly stable maleic anhydride hydrogenation catalyst includes the following steps: S1: Add the metal salt to the solvent and stir magnetically to obtain the precursor metal salt solution; S2: MFI zeolite was ultrasonically dispersed, added to a precursor metal salt solution, ultrasonically mixed, freeze-dried, and heated to 500-600℃ at a rate of 5-10℃ / min under an argon-hydrogen mixed atmosphere, and held at that temperature to obtain a maleic anhydride hydrogenation catalyst.

[0006] Further, in step S1, the metal salt is one or more of the following: nitrate metal salt, chloride metal salt, sulfate metal salt, acetylacetone metal salt, and acetate metal salt.

[0007] Further, in step S1, the solvent is one or more of deionized water, ethanol, chloroform, acetone, ethylene glycol, n-butanol, and isopropanol.

[0008] Furthermore, in step S1, the mass ratio of the metal salt to the solvent is 1:(15-30).

[0009] Furthermore, in step S2, the mass ratio of MFI zeolite to precursor metal salt solution is (3-5):10.

[0010] Further, in step S2, the preparation method of the MFI zeolite is as follows: the MFI zeolite-calcium carbonate composite material is placed in an acetic acid solution, stirred in a water bath, washed until neutral, dried, and calcined to obtain MFI zeolite.

[0011] Furthermore, in the preparation process of the MFI zeolite, the mass ratio of the MFI zeolite-calcium carbonate composite material to acetic acid is 1:(20-40).

[0012] Furthermore, the preparation method of the MFI zeolite-calcium carbonate composite material is as follows: Tetraethoxysilane, tetrapropylammonium hydroxide and aluminum isopropoxide are placed in deionized water, stirred and mixed, nano-calcium carbonate is added, stirred and mixed, heated to 120-140℃ and reacted for 48-72h, cooled and centrifuged, the solid is collected, washed and dried, and calcined to obtain the MFI zeolite-calcium carbonate composite material.

[0013] Furthermore, in the preparation process of the MFI zeolite-calcium carbonate composite material, the molar ratio of tetraethoxysilane, tetrapropylammonium hydroxide, aluminum isopropoxide and nano-calcium carbonate is 1:(0.1-0.2):(0.01-0.03):(0.1-0.3).

[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention introduces a high-entropy alloy as the metal active center of a maleic anhydride hydrogenation catalyst. Using five metal salts—nickel, copper, palladium, iron, and cobalt—as precursors, metal nanoparticles are formed through decomposition and reduction. This reaction process is mild and produces no harmful or difficult-to-treat substances. Nickel, palladium, and copper are commonly used active components in hydrogenation catalysis, while iron and cobalt can form stable solid solutions with the first three metals. The high-entropy alloy formed from the metal precursors can improve the selectivity of the main product and reduce side reactions, thereby improving the catalyst's reaction efficiency. Simultaneously, although palladium has good hydrogenation catalytic activity, it is expensive. Presence in the form of a high-entropy alloy can reduce the amount of precious metal used, lowering production costs, and the resulting maleic anhydride hydrogenation catalyst exhibits superior catalytic performance compared to precious metal catalysts. Furthermore, the severe lattice distortion of the high-entropy alloy increases the potential energy for atomic diffusion, hindering surface atomic diffusion and endowing the catalyst with higher stability. The multiple metal elements in the high-entropy alloy can work synergistically, regulating the electronic structure of the catalyst and providing abundant active sites for the maleic anhydride hydrogenation reaction, resulting in higher activity of the maleic anhydride hydrogenation catalyst.

[0015] 2. This invention uses MFI zeolite as a support for the maleic anhydride hydrogenation catalyst. In the synthesis of MFI zeolite, aluminum isopropoxide is introduced as an aluminum source, and nano-calcium carbonate is introduced as a hard template to prepare MFI zeolite with hierarchical pores. The introduction of aluminum isopropoxide gives MFI zeolite abundant acidic sites, promoting the adsorption and activation of maleic anhydride by the maleic anhydride hydrogenation catalyst. Acetic acid treatment removes nano-calcium carbonate, forming a hierarchical pore structure in the MFI zeolite, which promotes the diffusion and transport of maleic anhydride and its reaction products, avoids pore blockage, and improves the anti-carbon deposition ability of the maleic anhydride hydrogenation catalyst. Simultaneously, the high specific surface area and hierarchical pores of MFI zeolite not only increase the number of exposed acidic active sites and enhance the synergistic effect between metal and acid, improving the catalytic efficiency of the maleic anhydride hydrogenation catalyst; it also inhibits the migration and aggregation of active metals at high temperatures, leveraging the confinement effect of MFI zeolite on metal particles, inhibiting the abnormal growth of high-entropy alloy particles, thereby improving the activity and stability of the maleic anhydride hydrogenation catalyst. Furthermore, loading high-entropy alloys onto MFI zeolite enhances the synergistic effect between the metal and acid, while also increasing the contact opportunities between the active sites and the reactants, thereby improving the catalytic efficiency of the maleic anhydride hydrogenation catalyst.

[0016] 3. This invention first prepares MFI zeolite loaded with high-entropy alloys via an impregnation-liquid-phase reduction method, ensuring sufficient contact between the precursor metal salt solution and the MFI zeolite support, thus promoting uniform loading of the high-entropy alloy onto the MFI zeolite. Secondly, the precursor metal salt solution containing MFI zeolite is treated with freeze-drying technology, which not only effectively removes organic solvents but also inhibits the migration and aggregation of metal precursors caused by capillary forces, thereby obtaining highly dispersed metal nanoparticles. Finally, a gradual heating rate prevents rapid aggregation of metal particles, allowing for a strong interaction between the metal particles and the MFI zeolite support, thereby maintaining the stability of the maleic anhydride hydrogenation catalyst. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] In the following examples, the CAS number of nickel acetylacetone is 3264-82-2; the CAS number of copper acetylacetone is 13395-16-9; the CAS number of palladium acetylacetone is 14024-61-4; the CAS number of iron acetylacetone is 14024-18-1; the CAS number of cobalt acetylacetone is 14024-48-7; the CAS number of tetraethoxysilane is 78-10-4; the CAS number of tetrapropylammonium hydroxide is 4499-86-9; the CAS number of aluminum isopropoxide is 555-31-7; and the particle size of nano-calcium carbonate is 50 nm.

[0019] Example 1: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.1g nickel acetylacetone, 0.1g copper acetylacetone, 0.01g palladium acetylacetone, 0.05g iron acetylacetone, and 0.03g cobalt acetylacetone are added to 5ml ethanol-chloroform solution and magnetically stirred for 20min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.12 g tetrapropylammonium hydroxide and 0.01 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.05 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0 g of MFI zeolite-calcium carbonate composite material was placed in 20 ml of acetic acid solution, stirred in a water bath at 60 °C for 8 h, washed until neutral, dried at 105 °C for 12 h, and calcined at 450 °C for 3 h to obtain MFI zeolite. S4: 3.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 500 °C at a rate of 5 °C / min and held for 2 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0020] Example 2: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.15g nickel acetylacetone, 0.15g copper acetylacetone, 0.015g palladium acetylacetone, 0.075g iron acetylacetone, and 0.045g cobalt acetylacetone are added to 10ml ethanol-chloroform solution and magnetically stirred for 30min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.12 g tetrapropylammonium hydroxide and 0.01 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.05 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0 g of MFI zeolite-calcium carbonate composite material was placed in 20 ml of acetic acid solution, stirred in a water bath at 60 °C for 8 h, washed until neutral, dried at 105 °C for 12 h, and calcined at 450 °C for 3 h to obtain MFI zeolite. S4: 3.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 500 °C at a rate of 5 °C / min and held for 2 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0021] Example 3: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12g nickel acetylacetone, 0.12g copper acetylacetone, 0.012g palladium acetylacetone, 0.06g iron acetylacetone, and 0.036g cobalt acetylacetone were added to 10ml ethanol-chloroform solution and magnetically stirred for 40min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.12 g tetrapropylammonium hydroxide and 0.01 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.05 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0 g of MFI zeolite-calcium carbonate composite material was placed in 20 ml of acetic acid solution, stirred in a water bath at 60 °C for 8 h, washed until neutral, dried at 105 °C for 12 h, and calcined at 450 °C for 3 h to obtain MFI zeolite. S4: 3.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 500 °C at a rate of 5 °C / min and held for 2 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0022] Example 4: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12g nickel acetylacetone, 0.12g copper acetylacetone, 0.012g palladium acetylacetone, 0.06g iron acetylacetone, and 0.036g cobalt acetylacetone were added to 10ml ethanol-chloroform solution and magnetically stirred for 40min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.18 g tetrapropylammonium hydroxide and 0.02 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.096 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0 g of MFI zeolite-calcium carbonate composite material was placed in 30 ml of acetic acid solution, stirred in a water bath at 70 °C for 10 h, washed until neutral, dried at 105 °C for 12 h, and calcined at 500 °C for 4 h to obtain MFI zeolite. S4: 3.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 500 °C at a rate of 5 °C / min and held for 2 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0023] Example 5: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12g nickel acetylacetone, 0.12g copper acetylacetone, 0.012g palladium acetylacetone, 0.06g iron acetylacetone, and 0.036g cobalt acetylacetone were added to 10ml ethanol-chloroform solution and magnetically stirred for 40min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.12 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0g of MFI zeolite-calcium carbonate composite material was placed in 35ml of acetic acid solution, stirred in a water bath at 80℃ for 12h, washed until neutral, dried at 105℃ for 12h, and calcined at 500℃ for 5h to obtain MFI zeolite. S4: 3.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 500 °C at a rate of 5 °C / min and held for 2 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0024] Example 6: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12g nickel acetylacetone, 0.12g copper acetylacetone, 0.012g palladium acetylacetone, 0.06g iron acetylacetone, and 0.036g cobalt acetylacetone were added to 10ml ethanol-chloroform solution and magnetically stirred for 40min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.12 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0g of MFI zeolite-calcium carbonate composite material was placed in 35ml of acetic acid solution, stirred in a water bath at 80℃ for 12h, washed until neutral, dried at 105℃ for 12h, and calcined at 500℃ for 5h to obtain MFI zeolite. S4: 4.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 550 °C at a rate of 8 °C / min and held for 3 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0025] Example 7: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12g nickel acetylacetone, 0.12g copper acetylacetone, 0.012g palladium acetylacetone, 0.06g iron acetylacetone, and 0.036g cobalt acetylacetone were added to 10ml ethanol-chloroform solution and magnetically stirred for 40min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.12 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0g of MFI zeolite-calcium carbonate composite material was placed in 35ml of acetic acid solution, stirred in a water bath at 80℃ for 12h, washed until neutral, dried at 105℃ for 12h, and calcined at 500℃ for 5h to obtain MFI zeolite. S4: 5.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 600 °C at a rate of 10 °C / min and held for 4 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0026] Comparative Example 1: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: Add 0.4 g of copper acetylacetonate to 10 ml of ethanol-chloroform solution and stir magnetically for 40 min to obtain a pretreated copper acetylacetonate solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.12 g nano calcium carbonate was added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material. S3: 1.0g of MFI zeolite-calcium carbonate composite material was placed in 35ml of acetic acid solution, stirred in a water bath at 80℃ for 12h, washed until neutral, dried at 105℃ for 12h, and calcined at 500℃ for 5h to obtain MFI zeolite. S4: 5.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of pretreated copper acetylacetonate solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 600 °C at a rate of 10 °C / min and held for 4 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0027] Comparative Example 2: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12 g nickel acetylacetone, 0.12 g copper acetylacetone, 0.012 g palladium acetylacetone, 0.06 g iron acetylacetone, and 0.036 g cobalt acetylacetone were added to 10 ml ethanol-chloroform solution and magnetically stirred for 40 min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water, stirred and mixed, heated to 140 °C and reacted for 72 h, cooled and centrifuged, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite. S3: 5.0 g of MFI zeolite was ultrasonically dispersed for 2 h, 10 ml of precursor metal salt solution was added, ultrasonically treated for 1 h, freeze-dried, and heated to 600 °C at a rate of 10 °C / min and held for 4 h in an argon-hydrogen mixed atmosphere to obtain maleic anhydride hydrogenation catalyst.

[0028] Comparative Example 3: A method for preparing a highly stable maleic anhydride hydrogenation catalyst: S1: 0.12 g nickel acetylacetone, 0.12 g copper acetylacetone, 0.012 g palladium acetylacetone, 0.06 g iron acetylacetone, and 0.036 g cobalt acetylacetone were added to 10 ml ethanol-chloroform solution and magnetically stirred for 40 min to obtain a precursor metal salt solution; S2: 1.0 g tetraethoxysilane, 0.2 g tetrapropylammonium hydroxide and 0.025 g aluminum isopropoxide were placed in deionized water and stirred until well mixed. 0.12 g nano calcium carbonate and 10 ml precursor metal salt solution were added and stirred until well mixed. The mixture was heated to 140 °C and reacted for 72 h. After cooling and centrifugation, the solid was collected, washed and dried, and calcined at 550 °C for 5 h to obtain MFI zeolite-calcium carbonate composite material.

[0029] Hydrogenation experiment: The maleic anhydride hydrogenation catalysts prepared in the above examples and comparative examples were placed in 50 ml of tetrahydrofuran solution of 20 wt% maleic anhydride in a reaction vessel, and 0.2 g of maleic anhydride hydrogenation catalyst was added. The mixture was heated to 80 °C and the pressure was set to 2.0 MPa. The reaction was carried out in a hydrogen atmosphere for 2 h. After the reaction was completed, the liquid was collected and the components in the liquid were analyzed by gas chromatography. The conversion rate of maleic anhydride and the selectivity of succinic anhydride were calculated.

[0030] The experimental results are shown in Table 1.

[0031] Table 1 Performance test results of maleic anhydride hydrogenation catalyst

[0032] Conclusion: By adjusting and optimizing the proportions of the high-entropy alloy, MFI zeolite, and the process of supporting the high-entropy alloy with MFI zeolite, the maleic anhydride hydrogenation catalyst exhibits good catalytic activity and stability.

[0033] In Comparative Example 1, only copper was used as the active center loaded onto MFI zeolite, without the introduction of high-entropy alloys, which reduced the stability of the maleic anhydride hydrogenation catalyst. Simultaneously, the lack of a metal element with significantly different physicochemical properties reduced the electronic richness of the catalyst and decreased the number of active sites, thereby lowering the efficiency of the maleic anhydride hydrogenation reaction.

[0034] In Comparative Example 2, the absence of nano-calcium carbonate as a hard template during the preparation of MFI zeolite reduced the pore abundance and specific surface area of ​​the MFI zeolite, resulting in a decrease in the loading rate of the supported high-entropy alloy. Furthermore, the smaller pore size hinders the diffusion and transport of maleic anhydride and its products, reducing not only the catalytic efficiency of the maleic anhydride hydrogenation catalyst but also its resistance to carbon deposition, thus affecting the stability of the maleic anhydride hydrogenation catalyst.

[0035] In Comparative Example 3, a precursor metal salt solution was directly added during the hydrothermal synthesis of MFI zeolite. Calcination was then used to load a high-entropy alloy onto the MFI zeolite. The maleic anhydride hydrogenation catalyst prepared by this method exhibited reduced capacity for loading the high-entropy alloy. Furthermore, the presence of the precursor metal salt solution interfered with the crystallization process of the MFI zeolite, affecting the formation of its pore structure and thus reducing the stability and efficiency of the maleic anhydride hydrogenation catalyst.

[0036] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a highly stable maleic anhydride hydrogenation catalyst, characterized in that: Includes the following steps: S1: Add the metal salt to the solvent and stir magnetically to obtain the precursor metal salt solution; S2: MFI zeolite was ultrasonically dispersed, added to a precursor metal salt solution, ultrasonically mixed, freeze-dried, and heated to 500-600℃ at a rate of 5-10℃ / min under an argon-hydrogen mixed atmosphere, and held at that temperature to obtain a maleic anhydride hydrogenation catalyst.

2. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 1, characterized in that: In step S1, the metal salt is one or more of the following: nitrate metal salt, chloride metal salt, sulfate metal salt, acetylacetone metal salt, and acetate metal salt.

3. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 1, characterized in that: In step S1, the solvent is one or more of deionized water, ethanol, chloroform, acetone, ethylene glycol, n-butanol, and isopropanol.

4. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 1, characterized in that: In step S1, the mass ratio of metal salt to solvent is 1:(15-30).

5. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 1, characterized in that: In step S2, the mass ratio of MFI zeolite to precursor metal salt solution is (3-5):

10.

6. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 1, characterized in that: In step S2, the preparation method of the MFI zeolite is as follows: the MFI zeolite-calcium carbonate composite material is placed in an acetic acid solution, stirred in a water bath, washed until neutral, dried, and calcined to obtain MFI zeolite.

7. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 6, characterized in that: In the preparation process of MFI zeolite, the mass ratio of MFI zeolite-calcium carbonate composite material to acetic acid is 1:(20-40).

8. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 6, characterized in that: The preparation method of the MFI zeolite-calcium carbonate composite material is as follows: Tetraethoxysilane, tetrapropylammonium hydroxide and aluminum isopropoxide are placed in deionized water, stirred and mixed, nano-calcium carbonate is added, stirred and mixed, heated to 120-140℃ and reacted for 48-72h, cooled and centrifuged, the solid is collected, washed and dried, and calcined to obtain the MFI zeolite-calcium carbonate composite material.

9. The method for preparing a highly stable maleic anhydride hydrogenation catalyst according to claim 8, characterized in that: In the preparation process of the MFI zeolite-calcium carbonate composite material, the molar ratio of tetraethoxysilane, tetrapropylammonium hydroxide, aluminum isopropoxide and nano-calcium carbonate is 1:(0.1-0.2):(0.01-0.03):(0.1-0.3).

10. The maleic anhydride hydrogenation catalyst is prepared by the method according to any one of claims 1-9.